Criteria for selecting plus trees for protective forestry - Yu. I. Sukhorukikh; S. G. Biganova; A. P. Glinushkin; L. L. Sviridova (Новые технологии, 2023)
Protective forest strips are the basis of the environmental frame on sparsely wooded areas. To create such highly productive objects, the selection of the corresponding gene pool is required. Plus trees the representatives of this gene pool. The aim of the research is to develop criteria for highlighting plus trees for protective forestry, focused on the creation of plantings, the main parameter of which is the working height. 16 trial areas of cherry oak (Quércus róbur L.), black locust (Robinia Pseudoacia L.), green ash (Fraxinus lanceolata B.), European ash (Fraxinus excelsior L.), thorney locust (Gleditschia triacanthos L.), walnut (Juglans regia L.) have been laid out. A continuous recalculation of heights in 100–142 individuals have been recalculated on each trial area and their statistical indicators have been determined. The height of the trees had a normal or close to it statistical distribution at the studied objects. Data processing was carried out using the Stadia 8.0/Prof licensed program for Windows. The method of selecting plus trees has been proposed, the height of which should exceed the average one by 25% or more. A comparison of the proposed and well -known method has revealed that the proposed one can increase the breeding differential with instrumental selection by 48,25–53,78%, and with eye-instrumental selection by 31,15–41,39%. Criteria for trees of various selection categories have been developed. Due to different conditions, it is recommended to highlight plus trees separately in the extreme and mid-protective forest strips. With breeding inventory, it is also necessary to take into account the sanitary condition of the trees.